2017
DOI: 10.1515/acb-2017-0011
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of fructose and mannose – regulatory peptides signaling pathway in porcine epithelial oviductal cells (OECs) primary cultured long-term in vitro

Abstract: Advances in Cell BiologyAnalysis of fructose and mannose -regulatory peptides signaling pathway in porcine epithelial oviductal cells (OECs) primary cultured long-term in vitro AbstractThe morphological and biochemical modification of oviductal epithelial cells (OECs) belongs to the compound process responsible for proper oocytes transport and successful fertilization. However, the main mechanisms which regulated this process are still not entirely known. Moreover, the OECs metabolism, which may be identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Therefore, the goal of the present project is to describe molecular changes in OECs during primary in vitro long-term culture, through employing microarray approach. Previous studies have shown various aspects of OECs' morphological modifications and transcriptomic profile changes during in vitro cultivation [3][4][5]. The emphasis of the present study, is on groups of genes associated with nucleotide/ribonucleotide binding mechanism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the goal of the present project is to describe molecular changes in OECs during primary in vitro long-term culture, through employing microarray approach. Previous studies have shown various aspects of OECs' morphological modifications and transcriptomic profile changes during in vitro cultivation [3][4][5]. The emphasis of the present study, is on groups of genes associated with nucleotide/ribonucleotide binding mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…The results presented in previous studies are a valuable contribution for better understanding and elucidating many biochemical pathways and morphological/metabolomic factors existing in epithelial oviductal cells. Thus, employing a microarray approach, the molecular level processes identified were angiogenesis and blood vessels development [3], carbohydrates [4] and amino acids [5] metabolism. Furthermore, and plasticity of porcine cells associated with reproduction processes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial oviductal cell lines may be a valuable tool for better understanding and elucidating many biochemical pathways existing in oviducts. Our previous studies have shown various aspects of OECs' morphological modifications and transcriptomic profile changes during in vitro cultivation [8,9]. Therefore, employing a microarray approach in our study, we aimed to investigate the transcriptomic profile of OECs during long-term in vitro primary cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…For amplification, 2 μl of cDNA solution was added to 18 μl of QuantiTect ® SYBR ® Green PCR (Master Mix Qiagen GmbH, Hilden, Germany) and primers ( Table 1). One RNA sample of each preparation was processed without the RT-reaction to provide a negative control for subsequent PCR, where each sample processes in two technical repeats [17][18][19].…”
Section: Real-time Quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%